Impacto da desnutrição sobre o metabolismo e o desenvolvimento de alterações histopatológicas no intestino delgado de Gerbils (Meriones unguiculatus) experimentalmente infectados com Giardia lamblia - Luciana Laranjo Amorim Ventura (2012)
Giardiasis, intestinal infection caused by Giardia lamblia is an importante cause of diarrhea and intestinal malabsorption. Several studies have evaluated the influence of this disease on nutritional status. However, the impact of giardiasis in malnourished is speculative and there is no evidence that characterize malnutrition as an aggravating factor of the disease. This study assessed the metabolic and histopathological effects of G. lamblia infection in previously malnourished animals. We used 32 gerbils, female, 4-6 weeks, divided into 4 groups: Control (CT) and Control Infected (CTIn), fed a diet with 20% protein; Malnourished (DN) and Malnourished Infected (DNIn) with a 5% protein diet. On the 28th day of the experiment, the animals in groups and CTIn and DNIn were infected with G. lamblia, orally, remaining infected for 7 days, when all animals were euthanized and sampled blood, small intestine, liver and cecum content. The animals were weighed weekly using a scale. For biochemical evaluation, serum glucose, albumin, cholesterol and triglycerides were determined by enzymatic assay, and the total protein was performed by the Bradford method. The fractionation of the serum lipoproteins was performed by Fast Protein Liquid Chromatografy System. The determination of liver and cecal lipids was performed as described by Folch et al. The evaluation of oxidative stress was based on the determination of the concentration of thiobarbituric acid reactive substances and the dosage of catalase and superoxide dismutase. For histological analysis, the proximal small intestine was collected, fixed and intended for obtaining sections and staining with Hematoxylin & Eosin, Periodic Acid-Schiff and production of sections for immunohistochemistry. The villus height, mucus and trophozoites área were calculated using the software KS300 contained in Carl Zeiss image analyzer. Results were expressed as mean ± standard error, using the Shapiro-Wilk test to verify the normality of the sample and Analysis of Variance followed by Tukey test for comparison between experimental groups. We used the statistical package SPSS version 20.0, considering a significance level of 5%. It was observed that gerbils fed a low protein diet had significantly lower body weight, and reduced intake. There were no changes in serum parameters between groups. However, in lipoprotein profile, it was found that levels of protein and cholesterol were significantly lower in group DNIn compared to CT. The evaluation of liver lipids showed no difference between groups. However, it was observed that the group CTIn showed higher concentration of cholesterol in cecum contente than DN. The evaluation of oxidative stress was significantly different in catalase production, higher in DNIn than CT. The other parameters related to oxidative stress did not differ. The villus height was lower in the group DNIn when compared CTIn group. There was no statistical difference between the group and the group DN and DNIn. Regarding the area of mucus, we observed a statistical difference between groups CT and DNIn. Immunohistochemical analysis of the amount of Giardia trophozoites in the intestine of animals revealed no significant differences between groups and CTIn and DNIn. In summary, this study demonstrated that giardiasis in malnourished animals produced and metabolic changes in the structure of microvilli, suggesting worsening of the disease in malnourished.